Self-Management of Cardiac Pain in Women: A Meta-Summary of the Qualitative Literature. (September 2018) - Bjørnnes, Ann Kristin; Parry, Monica; Leegaard, Marit; Ayala, Ana Patricia; Lenton, Erica; Harvey, Paula; McFetridge-Durdle, Judith; McGillion, Michael H.; Price, Jennifer; Stinson, Jennifer; Watt-Watson, Judy
Symptom recognition and self-management is instrumental in reducing the number of deaths related to coronary artery disease (CAD) in women. The purpose of this study was to synthesize qualitative research evidence on the self-management of cardiac pain and associated symptoms in women. Seven databases were systematically searched, and the concepts of the Individual and Family Self-Management Theory were used as the framework for data extraction and analysis. Search strategies yielded 22, 402 citations, from which 35 qualitative studies were included in a final meta-summary, comprising data from 769 participants, including 437 (57%) women. The available literature focused cardiac pain self-management from a binary sex and gender perspective. Ethnicity was indicated in 19 (54%) studies. Results support individualized intervention strategies that promote goal setting and action planning, management of physical and emotional responses, and social facilitation provided through social support.